INOVASI PRODUK LABU SIAM TERHADAP PELUANG USAHA DESA BUTUH KIDUL WONOSOBO - Salis Irvan Fuadi; Fajar Fata Chilwasesa; Riyadi Setyawan; Ahmad Syarif Hidayat; Anisaul Khasanah; Siti Ati Zulfani; Anni Enggal Pangestuti; Ayu Anggit Nurmalasari; Lisa Fathiyyah; Eva Milla Shofana; Ofiani Khafidoh (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The KPM (Kuliah Pengabdian Masyarakat) Universitas Sains Al Qur'an carry out a community activity program in the Butuh Kidul Village. Butuh Kidul Village is one of the villages located in Kalikajar District, Wonosobo Regency. This village has the potential to produce vegetables. Vegetables that are widely produced are chayote. The KPM (Kuliah Pengabdian Masyarakat) students make product innovations from chayote into a more attractive product, namely chayote which is processed into candy. Candy is one of the food products that are liked by all ages. This activity was socialized through activities with the theme “Workshop on Marketing Strategy & Product Innovation from Pumpkin Siam”. This activity aims to take advantage of the potential of the Butuh Kidul Village community. By innovating through the use of chayote vegetables, it is possible to open UMKM (Micro, Small and Medium Enterprises) in the Butuh Kidul Village. The UMKM can have an impact on the Butuh Kidul Village community which can be a business opportunity for the Butu Kidul Village community. In this article, we explain how to process chayote into candy and promote marketing strategies through digital marketing.